Exploring Students’ Professional Identity Formation Through the Use of Technology: Let’s Jam! - Lindsey Moseley; Kimberly B. Garza; Heqin Yang (Journal of Teaching and Learning with Technology)
This manuscript will explore student pharmacists’ development of professional identity in a large classroom setting. PIF develops over time through an assortment of experiences. It can be a challenging topic for educators to teach. In a large-enrollment classroom, a small group activity utilizing Jamboard, a Google application, was designed to encourage first year student pharmacists to start exploring their professional identity. This manuscript describes our rationale and experience using this collaborative technology in a large class environment to help first year student pharmacists explore their identities in an active learning format. We will also explore advantages and disadvantages of using Jamboard as a tool for this application.